FUN DAY – MITIGASI BENCANA SDN 1 POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Pomahan Village is a village located in Pulung Subdistrict, Ponorogo Regency which is included in a high-lying area that is very vulnerable to natural disasters that will occur. In accordance with the problems that occur that Pomahan village is very vulnerable to natural disasters landslides. As we know that natural disasters of landslides do not have automatic warnings from an early age so it is important that there are efforts to minimize the impact caused by disasters carried out by all layers of the local community, commonly referred to as disaster mitigation. Disaster mitigation is a series of efforts to reduce disaster risk, both through physical development and awareness and capacity building in the face of disaster threats (Law 24/2007). The purpose of this activity is to change behavior and bring out insights or awareness from within as a result of changes in a positive mindset. The method used is planning, program implementation, and evaluation.